The ethnic prevalence of hypertension in a diabetic clinic. Issue 696 (October 1983) - Pacy, P. J.; Dodson, P. M.; Beevers, M.; Fletcher, R. F.; Taylor, K. G.
Abstract : Using the WHO criteria of hypertension, we have demonstrated that 40% of randomly selected diabetic clinic attenders under the age of 65 were hypertensive. Black diabetics had a significantly greater prevalence (P less than 0.001) of hypertension than either white or Asian diabetics. Hypertension was commoner in black and white females compared with males (P less than 0.001); in Asians this difference was not statistically significant. Systolic hypertension was the most common form in all ethnic groups. Only 38.7% of diabetics receiving antihypertensive therapy had normal blood pressure readings. Blood pressure measurement should therefore be routinely performed in all diabetic patients under the age of 65, particularly in females of all ethnic groups and in black males.